Gemcitabine–oxaliplatin as a bridge therapy toward autologous hematopoietic stem cell transplantation in infant-type brain tumors - Castelli, Barbara; Fonte, Carla; Tellini, Marco; Di Nicola, Marco; Guidi, Milena; Giunti, Laura; Tirinnanzi, Bianca; Marzano, Chiara; Buccoliero, Anna Maria; D’Incerti, Ludovico; Giordano, Flavio; Scagnet, Mirko; et al. (Frontiers in Oncology, 2025)
IntroductionIn neuro-oncological pediatric patients under 3 years of age, chemotherapy intensified to high doses (high-dose chemotherapy, HDC) represents the cornerstone to avoid the potential toxicity of radiotherapy. Combination treatment with gemcitabine–oxaliplatin (GemOx) was administered for infant- type cerebral tumors as a bridge toward autologous hematopoietic transplantation to achieve clinical and neuroradiological permissiveness to HDC and to raise the possibility of second-look neurosurgery. MethodsFrom May 2017 to May 2023, at Meyer Children’s Hospital IRCSS in Florence (Italy), four patients, with a median age of 19 months (with two high- grade gliomas, a metastatic medulloblastoma, and a choroid plexus carcinoma CNS WHO grade 3), were subjected to partial neurosurgical removal and induction therapy delivered according to the Italian program for malignant cerebral tumors under 3 years. To delay HDC, either for disease reassessment or for temporary unfitness, GemOx cycles were administered. Gemcitabine 1,000 mg/m2 and oxaliplatin 100 mg/m2 were given on day 1 every 21–28 days for one to six cycles. ResultsThe treatment was well tolerated overall, except for severe platelet hematological toxicity in a patient, which required dose reduction to 75%. After GemOx, one patient was also subjected to further neurosurgery. Bridge therapy made it possible to submit patients to HDC in safety, in permissive clinical conditions, and after assessment of disease stability. ConclusionIn infant-type cerebral tumors eligible for HDC, GemOx could be a possible strategy in the case of post-induction residual disease to exclude uncertain evolution or when waiting for clinical suitability for second surgery and intensified treatment. The therapy was overall safe and well tolerated. This approach resulted incisive in the therapeutic or palliative choice for extremely young patients with aggressive brain tumors.